The Accuracy of an Intraoperative Frozen Section for Premalignant Endometrial Pathology - Ergul Demircivi Bor; Esra Akdeniz; Yucel Nurettin Ceylan; Taner Gunay; Meryem Hocaoglu; Abdulkadir Turgut (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Abnormal uterine bleeding which is the most frequent complaint among pre- and postmenopausal women should be investigated to rule out endometrial cancer. An intra-operative frozen section can be taken to examine the suspicious of the malignancy. The study aims to investigate the accuracy of frozen section in suspicious of endometrial malignancy.